Pengembangan Media Komik Matematika Berbasis Nilai Karakter pada Materi Trigonometri di Kelas X SMA Negeri 1 Indralaya Utara - Manalu, Michael Amin; Hartono, Yusuf; Aisyah, Nyimas (Universitas Hamzanwadi, 2017)
This study aim to: (1) Produce media of math comics based on character values for trigonometry material on first grade (Class X) Senior High School which is valid and practical. (2) Determine the potential effects arise from development of mathematics comics media based on character values for trigonometry for first grade class toward student test result. The type of this research is Development Research, Formative Evaluation type. The subjects were student of Class X-1 of Public Senior High School No. 1 Indralaya Utara in academic year 2015/2016 totaling 30 students. Data collection techniques used is the walkthrough, observation and test. The results from this study are: (1) This research has produced a media of math comics based on character values for trigonometry material to first grade of senior high school which valid and practical. The validity drawn from the assessment result of validator in terms of content, construct, and language. Practicalities drawn from the results of a small group test where most student can well-use the media as planned. (2) Mathematics comics media based on character values can increase students character values. (3) Matematics comics media which is developed has a positive potential effect on students test results, it can be seen that the stundent achieving the Minimum Completeness Criteria Kriteria Ketuntasan Minimum (KKM) of Â 2,51 isÂ amounted to 83Â or as many as 25 students.